Effect of Organic Fertilizers on Soil Fertility and Peanut Yields - Mulyadi; Miki Satria; Rosman (Agriculture Journal, 2025)
To support environmentally sound agricultural practices, this study assessed the effectiveness of a single type of organic fertilizer applied at different dosage levels in optimizing the yield of groundnut (Arachis hypogaea L.). The methodology involved a Completely Randomized Design (CRD) field trial structured around four treatments: a control and three compost dosage levels, each executed in triplicate. Key performance indicators included plant morphological traits (height and number of pods) and harvest parameters (fresh pod weight and yield per hectare). Data analysis confirmed that all organic fertilizer applications led to statistically significant increases in groundnut growth and yield when compared to the untreated control. The highest dosage treatment (30 tons/ha) produced the most favorable outcome, with a fresh pod yield of 615 g/m². These improvements are attributed to the compost’s ability to enhance soil physical, chemical, and biological properties. This research supports the use of organic fertilizer as a sustainable strategy to improve groundnut productivity while maintaining environmental quality.